Pulse-Wave Analysis of Optic Nerve Head Circulation Is Significantly Correlated with Kidney Function in Patients with and without Chronic Kidney Disease - Tomoaki Shiba; Mao Takahashi; Takatoshi Maeno (Journal of Ophthalmology)
Aim. To determine whether there is a significant correlation between the optic nerve head (ONH) circulation determined by laser speckle flowgraphy (LSFG) and kidney function. Materials. Seventy-one subjects were investigated. The estimated glomerular filtration rate (GFR) and serum creatinine, cystatin C, and urinary albumin excretion were measured. The ONH circulation was determined by an analysis of the pulse wave of LSFG, and this parameter was named blowout time (BOT). Chronic kidney disease (CKD) was defined to be present when the estimated GFR was <60 mL/min per 1.73 m2. Pearson’s correlation coefficients were used to determine the relationship between the BOT and the kidney function. We also examined whether there were significant differences in all parameters in patients with and without CKD. Results. BOT was significantly correlated with the level of creatinine (r=-0.24, P=0.04), the estimated GFR (r=0.42, P=0.0003), cystatin C (r=-0.29, P=0.01), and urinary albumin excretion (r=-0.29, P=0.01). The BOT level in subjects with CKD was significantly lower than that in subjects without CKD (P=0.002). Conclusion. BOT in ONH by LSFG can detect the organ damage such as kidney dysfunction, CKD.